Season of birth, neonatal vitamin D status, and cardiovascular disease risk at 35 y of age: a cohort study from Sweden. Issue 3 (8th January 2014) - Tornhammar, Per; Ueda, Peter; Hult, Martin; Simila, Henry; Eyles, Darryl; Norman, Mikael
ABSTRACT: Background: Lower vitamin D status during gestation may be associated with cardiovascular disease risk later in life. No studies have assessed this hypothesis with a follow-up time reaching beyond childhood. Objective: The objective was to assess the link between season of birth, neonatal 25-hydroxyvitamin D3 [25(OH)D3 ] status, and adult cardiovascular disease risk. Design: Markers of cardiovascular and metabolic disease risk were measured in 284 subjects aged 35 y, born either at the end of the winter or at the end of the summer of 1975. In 275 of these 284 subjects, concentrations of neonatal 25(OH)D3 were measured in dried blood samples by using a highly sensitive liquid chromatography–tandem mass spectroscopy method. Results: Subjects born after the winter had lower neonatal 25(OH)D3 concentrations than did those born after the summer (31.5 compared with 48.5 nmol/L; P < 0.001). In regression analyses adjusted for sex, season of birth, postnatal age at neonatal sample collection, preterm birth, maternal age, education, smoking, fish consumption per week, exercise per week, and current 25-hydroxyvitamin D, higher neonatal 25(OH)D3 (per 50 nmol/L) was associated with 25.8% (95% CI: 1.0%, 58.4%) higher fasting insulin in adult life, 29.6% (5.1%, 58.4%) higher triglycerides, and 4.64 (95% CI: 1.93, 7.36) mmol/L higher serum cholesterol in women. Neonatal 25(OH)D3 (per 1 nmol/L) was directly associated with risk of adult overweight (OR: 1.03; 95% CI: 1.01, 1.05) and with adult obesity in women (OR: 1.09; 95% CI: 1.02, 1.17). Neonatal 25(OH)D3 was not associated with adult aortic pulse wave velocity, blood pressure, fasting glucose, HDL, LDL, or C-reactive protein. Season of birth was not associated with any of the adult outcomes. Conclusions: Higher neonatal 25(OH)D3 was associated with higher fasting insulin, triglyceride, and cholesterol (in women) concentrations and with a higher risk of overweight at 35 y of age but not with other adult cardiovascular disease risk factors.